EVOLUTION OF DISTILLATION FROM ANCIENT ERA TO MODERN ERA - Tanwar, Pramila (SCHOOL SCIENCE, 2025)
The history of distillation has often been traced back to the Greeks and later to the Arabs for its origin according to the traditional belief. History of distillation is linked to the development of scientific and alchemical knowledge, playing a vital role in modern chemistry. The objective of this article is to re-examine the early history, origin of distillation by studying the various forms of stills in different regions across the world, including India, to study the influence of various alchemists on the advancement of distillation techniques, review the textual evidence, explore the evolution of distillation from ancient era to the modern era by focusing on its applications for the production of alcohol, extracting essential oils and others, based on historical records